Analisis Studi Kelayakan Pendirian BPRS Patriot Cabang Bekasi Timur - Husnul Khotimah Sylvia; Muhammad Asmawi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2019)
The success of BPRS in providing service to small and medium businesses is due to uts location close to people in need, simple service procedures that prioritize personal approaches and flexibility in financing patterns and models and more importantly, that BPRS are banks that use systems and principles Sharia. BPRS Patriot City Bekasi is a sharia banking service company, it will not be possible to avoid the reality of competition in the banking service industry wich is increasing. In connection with the quality of service in retaining customers and expanding marketing networks, BPRS Patriot Kota Bekasi should develop offices. The establishment of the Bekasi BPRS Patriot Branch Office is the righ choice. This is very good for the development of the BPRS but will also be able to contribute to the performance of the BPRS in general as well as for the economy of the community especially in the working area of the BPRS Patriot Bekasi. The results of the SWOT analysis are taken from various aspects. As such, the BPRS Patriot Bekasi is considered feasible and capable of establishing Branch Offices.